Risk communication and human biomonitoring: which practical lessons from the Belgian experience are of use for the EU perspective? - Loots Ilse; Morrens Bert; Keune Hans (BMC, 2008)
Abstract Background In order to investigate and monitor environmental health in Flanders (the Dutch speaking part of Belgium), the Flemish government funded the Centre of Expertise for Environment and Health, which started a human biomonitoring campaign in 2001. In addition to environmental health experts measuring environmental pollutants and health effects in human beings, social scientific experts at the Centre focus on risk communication associated with the human biomonitoring campaign. Methods In the literature about risk communication an evolution can be traced from traditional, one-way communication, restricted to the dissemination of information from experts to the public, to more modern, two-way risk communication, with a focus on participation and cooperation between scientists, policy-makers and the public. Within the Centre of Expertise for Environment and Health this discourse was first translated into some general principles and guidelines for external communication, at a 'Ten Commandments level'. These principles needed to be incorporated in the day-to-day practice of human biomonitoring research. Results The social scientific experts at the Centre developed a combined risk communication strategy. On the one hand the strategy consists of traditional risk communication for external communication purposes, for example information meetings and digital newsletters. On the other hand it consists of a step by step approach of incorporating more modern risk communication, for example a risk perception questionnaire, dialogical experiments for involving local stakeholders, and an action-plan for interpreting results for policy making. Conclusion With a parallel strategy of traditional and modern communication, of external and internal reflection, and through different social scientific projects, the Flemish Centre of Expertise of Environment and Health incorporates risk communication in the day-to-day practice of human biomonitoring research. A direct and continuous involvement of the social scientist, an openness between all colleagues involved, and the awareness of a fine balance between quality and practicability are important success factors. These lessons may be helpful and inspirational for a European human biomonitoring project.